Effect of microinflammation on assessment of iron metabolism in peritoneal dialysis patients - FAN Zhe; JIANG Xiao; WU Yong-gui; WANG Juan; QI Xiang-ming (Linchuang shenzangbing zazhi)
Objective To analyze the correlation between C-reactive protein(CRP) and indicators of iron metabolism,and explore the effect of microinflammatory state on iron metabolism in peritoneal dialysis patients.Methods Seventy-nine patients undergoing continuous ambulatory peritoneal dialysis(CAPD) from our hospital were enrolled in the study.The data of age,sex,PD duration,systolic blood pressure(SBP),diastolic blood pressure(DBP),Kt/V,hemoglobin,CRP,serum iron(SI),transferrin saturation(TSAT),serum ferritin(SF),serum albumin,serum creatinine,and urea nitrogen were collected.The patients were divided into group A(CRP≤8 mg/L) and group B(CRP>8 mg/L) according to the levels of CRP.The patients were also divided into group C(SF<500 μg/L) and group D(SF≥500 μg/L) according to the levels of SF.Comparison of data between groups(A and B,or C and D) was performed using the Student t-test for continuous parametric data.The correlation between CRP and SI,TSAT,SF,SBP or DBP was analyzed by Pearson correlation analysis.Results(1) As compared with group A,the levels of SF were significantly increased(t =- 2.976,P<0.01),and those of SI,TSAT,SBP and DBP were significantly decreased in group B(t= 3.743,P<0.01 i t= 2.420,P = 0.018;t = 2.181,P = 0.032;2 = 2.328,P = 0.023 respectively).There was no significant difference in hemoglobin between group A and group B(t = 0.680,P =0.498).(2) No significant difference was found in the clinical data between group C and group D such as age,sex,PD duration,SBP,DBP,Kt/V,hemoglobin,CRP,SI,TSAT,serum albumin,serum creatinine,and urea nitrogen.(3) Pearson correlation analysis revealed that CRP had a positive correlation with SF(r = 0.460,P<0.01) and a negative correlation with SI(r =- 0.350,P = 0.002).Conclusions The indicators of iron metabolism are constantly affected by microinflammatory state in CAPD patients.Therefore,the combined tests of SI,TSAT,SF and CRP may favor the correct assessment of iron metabolism state.